DESIGNING CROSSWORD PUZZLE TO IMPROVE STUDENTS’ VOCABULARY MASTERY OF THE THIRD SEMESTER IN ENGLISH EDUCATION DEPARTMENT STUDENT OF UIN ALAUDDIN MAKASSAR - Sukirman ,; Asti Astuti Ningsih (ETERNAL (English, Teaching, Learning and Research Journal), 2016)
: This research design Crossword Puzzle in the Third Semester of English Education Department at UIN Alauddin Makassar. The objective of this research was to design crossword puzzle to improve students’ vocabulary mastery. It was conducted in the third semester students in the English Education Department of UIN Alauddin. The significance of this research were for students, teachers, and other research. For students with their research will facilitate the student in improving their vocabulary. In addition, this study was designed to produce teaching materials, especially in vocabulary lesson used crossword puzzle. For teachers, this research can be useful to produce media that can facilitate teachers in presenting the lesson. For other researchers, the results of this study can be used as a comparison, especially in terms of the development of teaching materials in vocabulary. The research design of this research was Research & Development (R&D). It applied model R&D adapted from Borg & Gall model. The steps of the model were needed assessment, designing the product, validating product, revising initial product, trying out product, final revising product, and the last final product. The types of data of this research were quantitative and qualitative data. The research instruments were questionnaire and research judgments.